(untitled) (Journal of Applied Science and Engineering A, 2021)
We have investigated Sb interface on the single-domain vicinal Si(001) surface inclined by 4° toward [110] direction using scanning tunneling microscopy and high-resolution synchrotron photoelectron spectroscopy. This vicinal Si(100)-4° off surface is reconstructed to form nine-dimer-wide single-domain (001)-p(2×2) terraces separated by rebonded DB double-layer steps, when the Si-dimer rows perpendicular to the steps. By 2ML Sb-deposition at RT and subsequent postannealing at 500°C, the Si surface has been covered by Sb-dimer rows whose direction is parallel to the steps composed of SA and SB (Sb rebounded atom) steps. And all the Si 2p components related to the clean surface have disappeared, while the Sb-Si interfacial component has been identified. Such a component is mainly due to charge transfer between Si and Sb atoms at the top layer. Based on these results, it has been concluded that Sb atoms passivate the vicinal Si(001)-4° off surface through forming 1ML Sb layers composed of Sb dimers and Sb rebonded atoms.